Analyzing Impact of Balinese Regional Policies Vertical Building Development Limitation - Bagus, Putu Genta Ananda Este (Universitas Ibn Khaldun Bogor, 2025)
Nowadays, ancient culture practices in which then derived into current practices mostly answer the problem in all side of things. Balinese culture is not that different from all of them. Most Balinese people have general understanding of tri hita karana (three ways to reach harmony) concept as the root of Balinese culture. The concept itself explains around how to reach harmony by making mutual relationship with nature, social lives, and the divine. From that, people in Bali derived the concept into various things including urban and rural planning. tri angga (three bodies) is one of the concepts that states regional planning must follow certain rules to reach harmony. This bodies consist of temple, people's working area, and nature which symbolizes the level of consecration of human bodies. From this concept, Bali regional development policies then adjusted to preserve cultural value of Bali. This policies states that any building built within the region must follow the regulation to get the certificate to further develop a project/building. In building development part there is one interesting regulation that states certain type of building cannot planned or developed past the height of a coconut tree, which then reworded into fifteen meters. But this case make development and/ or urban expansion move into more horizontal way. Horizontal development was a way to compensate the same amount of people that will use the facility compared to develop vertically, in turns use large area of landmass that can accelerate the speed of land decline and green open spaces which Balinese people sought to protect. This acceleration also accompanied with small island area, static land size, and sea level rise from climate change. This research aims to find whether existence of both limitation and the speed of land development can proceed sustainably